Acute gastroenteritis hospitalizations after implementation of universal mass vaccination against rotavirus. Issue 13 (17th March 2020) - Kõivumägi, Kadri; Toompere, Karolin; Soeorg, Hiie; Kallas, Eveli; Jõgeda, Ene-Ly; Huik, Kristi; Lutsar, Irja; ,
Highlights: Universal rotavirus vaccination reduces rotavirus gastroenteritis hospitalizations. Universal rotavirus vaccination reduces overall AGE hospitalizations. Rotavirus vaccines are effective regardless of prevailing genotype in a population. Abstract: Background: Estonia implemented rotavirus universal mass vaccination (RV UMV) in July 2014. We aimed to describe changes in acute gastroenteritis (AGE) hospitalization during RV seasons before (2007–2013) and after (2015–2018) RV UMV and compare patient profile of hospitalized AGE patients aged 0–18 years during first two consecutive RV seasons 2015 vs 2016. Methods: We described AGE hospitalization patterns pre-and post-vaccine era using Estonian Health Insurance Fund (HIF) database. During a two-year observational multicenter study in seven Estonian hospitals from 01st of February 2015 to 30th August 2016 we assessed patient profile of all patients who met pre-determined AGE criteria. Results: In post-vaccine era AGE hospitalization rate decreased from 10 to 8 per 1000 population (RR 0.81, 95% CI 0.79–0.83) compared to pre-vaccine era. Decreased RV seasonal activity, 81% (95% CI 77–84) and 55% (95% CI 52–58) reduction of rotavirus gastroenteritis (RVGE) hospitalization among age groups <1 and 1–4, respectively and upsurge of norovirus gastroenteritis (NoVGE) hospitalizations (RR = 1.8; 95% CI 1.6–1.9) was seen. In the multicenter observational study, among 2249 AGE patients hospitalized median age of RVGE patients increased from 2 to 3 years (p < 0.01) and duration of hospital stay decreased among RVGE, NoVGE and other GE patients during two consecutive RV seasons. According to Vesikari Clinical Severity Scoring System statistically significant change of severity score distribution in two RV seasons was seen (p < 0.001) with trend towards less severe AGE hospitalizations; 82.5% vs 70.5% severe cases in 2015 vs 2016, respectively. Conclusion: RV UMV lead to immediate and sustainable reduction of hospitalizations due to RVGE in children aged <4 years and reduction of overall AGE accompanied with the decrease in the severity of hospitalized children.